The influence of content, influencer, and experiential marketing on customer engagement of online game applications - Desak Made Febri Purnama Sari; Sari Dewi Aprialita (Universitas Pendidikan Nasional, 2023)
This study was motivated by the rapid development of online games in Indonesia, particularly in Denpasar City. It could be seen from the download increasement of online games on a number of platforms such as Play Store, Appstore, and also steam chart. Online games nowadays were easy to be played anywhere and anytime with good image quality. Additionally, the government really appreciated and supported the world of online gaming sports or well-known as e-sports. The purposes of this study were; 1) to determine the effect of content marketing on the process of forming customer engagement in online game applications, 2) to find out the influence of influencers on the process of forming customer engagement in online game applications, 3) to determine the effect of experiential marketing on the process of forming customer engagement in online game applications, and 4) to find out whether there is a simultaneous influence between content marketing, influencers, and experiential marketing to customer engagement on online games in Denpasar. This study used the quantitative data analysis method. Data collection techniques used were observation and questionnaires. Then, the data were analyzed by using SPSS. Partially, content adoption, influencer, and experiential marketing have a positive and significant influence on customer engagement in online games in Denpasar. The results of this study indicated that (1) variable content has a positive and significant effect on customer engagement, (2) influencer variables have a positive and significant effect on customer engagement, (3) experiential marketing variables have a positive and significant effect on customer engagement, and (4) content, influencers, and experiential marketing variables have a positive and significant effect on customer engagement.